2017
DOI: 10.1111/tan.12966
|View full text |Cite
|
Sign up to set email alerts
|

Typing and copy number determination for HLA‐DRB3, ‐DRB4 and ‐DRB5 from next‐generation sequencing data

Abstract: Our method for DRB3/4/5 typing has high accuracy. It is a good supplement to regular HLA typing and could help in disease studies, medical applications and human population diversity studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…For example, the observed variation in gene expression within and between populations involving functional paralogous HLA-DRB genes is likely to be accounted for by the variable number of HLA-DRB loci dependent on haplotype that vary in frequency across populations ( Gonzalez-Galarza et al , 2015 ; Zhang et al , 2017 ). This variation is reflected in the occurrence of these genes among the reference haplotypes ( HLA-DRB1 is present in seven out of the eight available reference haplotypes, whereas HLA-DRB3 is only present on COX and QBL, HLA-DRB4 on MCF and SSTO and HLA-DRB5 on PGF) and in population studies where, for example, African ancestry populations have high frequency of HLA-DRB3 and low HLA-DRB4 ( Zhang et al , 2017 ) consistent with our observations at the level of gene expression. We also provide estimates of differences in gene expression specific to individual HLA types involving six classical HLA genes, with HLA typing information extracted from RNA-seq data by HLA typing tools.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the observed variation in gene expression within and between populations involving functional paralogous HLA-DRB genes is likely to be accounted for by the variable number of HLA-DRB loci dependent on haplotype that vary in frequency across populations ( Gonzalez-Galarza et al , 2015 ; Zhang et al , 2017 ). This variation is reflected in the occurrence of these genes among the reference haplotypes ( HLA-DRB1 is present in seven out of the eight available reference haplotypes, whereas HLA-DRB3 is only present on COX and QBL, HLA-DRB4 on MCF and SSTO and HLA-DRB5 on PGF) and in population studies where, for example, African ancestry populations have high frequency of HLA-DRB3 and low HLA-DRB4 ( Zhang et al , 2017 ) consistent with our observations at the level of gene expression. We also provide estimates of differences in gene expression specific to individual HLA types involving six classical HLA genes, with HLA typing information extracted from RNA-seq data by HLA typing tools.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, we sought to predict the number of HLA-DRB3 -DRB4, and -DRB5 copies prior to assessing allele accuracy. Zhang et al previously showed that copy numbers could be predicted from targeted sequencing using the ratio of HLA-DRB345 reads to HLA-DRB1 reads (25). Using a similar approach, we trained a K-nearest neighbor (kNN) classifier to predict the number of HLA-DBR3, -DRB4, and -DRB5 alleles based on their relative read abundance (Figure S3A).…”
Section: Increasing Accuracy Of Hla-drb345 Predictionsmentioning
confidence: 99%
“…To address this, we sought to predict the number of HLA-DRB3 -DRB4, and -DRB5 copies prior to assessing allele accuracy. Zhang et al previously showed that copy numbers could be predicted from targeted sequencing using the ratio of HLA-DRB345 reads to HLA-DRB1 reads [24]. Using a similar approach, we trained a K-nearest neighbor (kNN) classifier to predict the number of HLA-DBR3, -DRB4, and -DRB5 alleles based on their relative read abundance (Figure S3A).…”
Section: Increasing Accuracy Of Hla-drb345 Predictionsmentioning
confidence: 99%